Differences in prevalence and management of chronic kidney disease among T2DM inpatients at the grassroots in Beijing and Taiyuan: a retrospective study - Lingwang An; Dandan Wang; Xiaorong Shi; Yali He; Yaujiunn Lee; Juming Lu (BMC, 2023)
Abstract Purpose Chronic kidney disease (CKD) has been one of the most common complications in type 2 diabetes mellitus (T2DM) patients. This retrospective study aimed to investigate the regional differences in the prevalence and management of CKD in T2DM inpatients from two grassroots hospitals in Beijing and Taiyuan. Methods The sociodemographic status, health history, lifestyle information, biochemical parameters and drug choices of the patients were collected from the Diabetes Care Information System using a retrospective cross-sectional analysis. The presence of CKD was defined as albuminuria (urine albumin-to-creatinine ratio of ≥ 30 mg/g) and/or as a reduced estimated glomerular filtration rate (< 60 ml/min/1.73 m2). Results 858 patients with T2DM in Beijing and 1,085 patients with T2DM in Taiyuan were included, with a median age of 61.0 and 61.9 years, respectively. The duration of diabetes was 10.5 and 10.3 years, respectively. The prevalence of CKD in Beijing (39.2%) was significantly higher than in Taiyuan (22.4%). The overall ABC control (A = haemoglobin A1c; B = blood pressure; C = cholesterol) in both the Beijing and Taiyuan groups were not ideal. Patients with CKD tended to use insulin, renin-angiotensin-aldosterone system (RAAS) inhibitors, sodium-glucose cotransporter-2 inhibitors (SGLT-2i) and dyslipidaemia therapy in Taiyuan than in Beijing. The actual proportion of carbohydrate, fat and protein in calories was 49.6%:35.4%:14.4% in Beijing and 61.5%:27.8%:10.8% in Taiyuan. Conclusions The higher prescription rates of RAAS inhibitors, SGLT-2i and dyslipidaemia therapy may underlie the fluctuations in the prevalence of CKD in Beijing or Taiyuan. Intensive insulin therapy and personal nutritional guidance, along with the extensive use of RAAS inhibitors, SGLT-2i and dyslipidaemia therapy during follow-up, can all play a positive role in the management of CKD in patients with T2DM in both Beijing and Taiyuan.